2018
DOI: 10.1088/1361-6560/aacb65
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and dosimetric evaluations of atlas-based segmentation methods of MR images in the head and neck region

Abstract: Owing to its excellent soft-tissue contrast, magnetic resonance (MR) imaging has found an increased application in radiation therapy (RT). By harnessing these properties for treatment planning, automated segmentation methods can alleviate the manual workload burden to the clinical workflow. We investigated atlas-based segmentation methods of organs at risk (OARs) in the head and neck (H&N) region using one approach that selected the most similar atlas from a library of segmented images and two multi-atlas appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 50 publications
2
57
0
4
Order By: Relevance
“…The study was limited to three soft tissue organs. Kieselmann et al 26 took an atlas approach to segment the parotids, spinal cord, and mandible on T1-weighted MR. Other than the limited organs in these studies, they were based on high-field diagnostic multiparametric MR images while MR-guided radiation therapy more often relies on lower magnetic fields and is more limited in variety of sequences. To our best knowledge, there has not been an automated segmentation study on the low-field H&N MR images from MR-guided radiotherapy systems.…”
Section: Introductionmentioning
confidence: 99%
“…The study was limited to three soft tissue organs. Kieselmann et al 26 took an atlas approach to segment the parotids, spinal cord, and mandible on T1-weighted MR. Other than the limited organs in these studies, they were based on high-field diagnostic multiparametric MR images while MR-guided radiation therapy more often relies on lower magnetic fields and is more limited in variety of sequences. To our best knowledge, there has not been an automated segmentation study on the low-field H&N MR images from MR-guided radiotherapy systems.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that although it is important to quantify the degree of variation or uncertainty of the contouring, it is more important to determine the dose difference and clinical impact [10,11,14,16,17,22,23]. In earlier work, van Rooij et al [17] studied the accuracy of automatic delineation of organs at risk in the head and neck region based on deep learning techniques while using geometric indices and dosimetric indices, and they analyzed the correlation between the geometric index SDC (mean value of the DSC) and dose difference.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is considerable variability between them, and different auto-segmentation studies use different geometric indices to evaluate the contouring results; further, different indices have different properties [12][13][14]. Under the assumption of a reference contour, the method for clinically assessing the accuracy of radiotherapy (RT) contours is to determine and predict the deviation of its dosimetric indices based on the dose distribution of the radiation treatment plan [10,[15][16][17]. The relationships between geometric indices and dosimetric indices are yet to be further studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obrazowanie MRI, przed zastosowaniem hybryd MR-RT, było wykorzystywane głównie jako pomocnicze do wyznaczenia objętości napromienianej na skanach CT po wcześniejszej fuzji obrazów. Obecnie systemy pracujące w oparciu o MR-only RT umożliwiają skanowanie pacjenta bezpośrednio przed lub w trakcie leczenia i dostosowanie planu zgodnie ze zaktualizowanymi informacjami na temat anatomii pacjenta dla tej samej frakcji leczenia [6]. Do wyznaczenia nowych konturów targetu i narządów krytycznych na skanach MR możemy wybrać poniższe możliwości:…”
Section: Wyznaczenie Konturówunclassified